English language learning in Malaysian schools: A comparison between government and private schools teachers’ teaching methodologies to improve student learning - Ramakrishnan, Shalini; Selvarajoo, Paul Chandra Bose; Govindarajoo, Mallika Vasugi V. (Edelweiss Applied Science and Technology, 2025)
English plays a pivotal role globally, impacting key sectors such as education, business, and culture. In Malaysia, despite ongoing shifts in the national education system, English remains a core and compulsory subject in schools. This study explores the differences in teaching methods between government and private school teachers, aiming to identify effective strategies that enhance student learning in English language classrooms. Employing a mixed-methods approach, data were collected through an online survey involving 20 primary and secondary school teachers. The survey included a combination of yes/no questions, rating scales, multiple-choice items, and open-ended responses. Demographic variables such as teaching experience, English proficiency, and professional training were also examined to contextualize the findings. Results underscore the pressing need for educational reform, particularly the integration of interactive and student-centered teaching approaches to boost student engagement and learning outcomes. Most respondents expressed a strong commitment to quality education, especially in the context of English language instruction. Major issues included heavy workloads, large class sizes, inconsistent implementation of the Dual Language Programme (DLP), outdated curricula, and limited infrastructure—particularly in under-resourced schools. Teachers expressed the need for stronger institutional support, targeted professional development, curriculum reform, and improved assessment practices. The study offers practical implications for novice teachers in designing effective curricula and instructional strategies that foster active participation and deeper learning among students.